(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In Latvia so far there have not been made comprehensive studies to provide balance function diagnostics for people with disabilities, which would have to continue with further creation of appropriate system. However, Latvian researchers developed methods and technology for the rehabilitation and health improvement. At the same time it is also recognized that there is a lack of dedicated efficient and widely accessible for patients systems, equipment and tools to make balance function and dysfunction diagnostics, as well an improvement of the patients’ movement capabilities. This position paper gives a brief overview about the latest technical engineering solution trends and developments in the world, which could be suited and developed to create the conformable new, rather simple, accessible and cheap system. Such system will have to ensure the diagnostics of balance functions of the persons with disabilities and encourage them to use mentioned equipment for testing and training of their balance and movement functionality.